2007
DOI: 10.1016/j.yhbeh.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Raised salivary testosterone in women is associated with increased attraction to masculine faces

Abstract: Women's preferences for masculinity in men's faces, voices and behavioral displays change during the menstrual cycle and are strongest around ovulation. While previous findings suggest that change in progesterone level is an important hormonal mechanism for such variation, it is likely that changes in the levels of other hormones will also contribute to cyclic variation in masculinity preferences. Here we compared women's preferences for masculine faces at two points in the menstrual cycle where women differed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
142
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(158 citation statements)
references
References 29 publications
13
142
3
Order By: Relevance
“…In line with previous work investigating sexually-dimorphic face preferences (DeBruine et al, 2006;Jones et al, 2007;Welling et al, 2007Welling et al, , 2008Welling et al, , 2013, the present study used prototype-based image transformations in order to objectively manipulate sexual dimorphism of 2D shape in facial images, creating masculinized and feminized images of the same individual that are matched for other variables (e.g., skin color, identity, texture: Rowland & Perrett, 1995). Briefly, prototype images (i.e., an average male face and an average female face) were created by averaging a group of male and a group of female images via widely-used computational methods in face perception studies (e.g., Jones et al, 2005;Penton-Voak et al, 1999;Welling et al, 2007). Once prototypes are established, individual stimuli are created by adding or subtracting a percentage of the differences in position between the prototype images from the corresponding points on a third face (for technical details see Rowland & Perrett, 1995;Tiddeman, Burt, & Perrett, 2001).…”
Section: Experiments 1 Methodssupporting
confidence: 90%
“…In line with previous work investigating sexually-dimorphic face preferences (DeBruine et al, 2006;Jones et al, 2007;Welling et al, 2007Welling et al, , 2008Welling et al, , 2013, the present study used prototype-based image transformations in order to objectively manipulate sexual dimorphism of 2D shape in facial images, creating masculinized and feminized images of the same individual that are matched for other variables (e.g., skin color, identity, texture: Rowland & Perrett, 1995). Briefly, prototype images (i.e., an average male face and an average female face) were created by averaging a group of male and a group of female images via widely-used computational methods in face perception studies (e.g., Jones et al, 2005;Penton-Voak et al, 1999;Welling et al, 2007). Once prototypes are established, individual stimuli are created by adding or subtracting a percentage of the differences in position between the prototype images from the corresponding points on a third face (for technical details see Rowland & Perrett, 1995;Tiddeman, Burt, & Perrett, 2001).…”
Section: Experiments 1 Methodssupporting
confidence: 90%
“…These values are similar to those reported in previous research using a similar sample (e.g. Deady, Smith, Sharp, and Al-Dujaili 2006;Welling et al 2007). Spearman's rank correlations indicated that neither the time of sampling (r=−.01, p=.92) nor participants' age (r= −.14, p=.23) were related to measured testosterone levels.…”
Section: Descriptive Analysessupporting
confidence: 91%
“…Likewise, further studies could consider the influence of cycle phase in regularly cycling women, as there is some evidence to suggest that testosterone increases near to ovulation (e.g. Alexander, Sherwin, Bancroft, and Davidson 1990;Bloch, Schmidt, Su, Tobin, and Rubinow 1998;Dabbs 1990;Morris, Udry, KhanDawood, and Dawood 1987;Schultheiss, Dargel, and Rohde 2003;Welling et al 2007, but see Dabbs 1990;Liening, Stanton, Saini, and Schultheiss 2010;Schultheiss et al 2003), although this effect is unlikely to be large since daily fluctuations (due to circadian rhythm) and seasonal fluctuations in testosterone are often greater than cyclical changes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, preferences for masculine characteristics in men's faces tend to be stronger when women's testosterone (Bobst et al, 2014;Welling et al, 2007) and/or estradiol (Roney & Simmons, 2008;Roney et al, 2011) levels are high. While these studies focused on women's judgments of the attractiveness of men's faces, other studies have investigated the effects of changes in women's hormone levels on their perceptions of emotional expressions in adult faces Derntl et al, 2008;Guapo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%